2014
DOI: 10.1109/tnsre.2013.2296334
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automatic Control of Paraplegic FES Pedaling Using Higher-Order Sliding Mode and Fuzzy Logic Control

Abstract: In this paper, a fully automatic robust control strategy is proposed for control of paraplegic pedaling using functional electrical stimulation (FES). The method is based on higher-order sliding mode (HOSM) control and fuzzy logic control. In FES, the strength of muscle contraction can be altered either by varying the pulse width (PW) or by the pulse amplitude (PA) of the stimulation signal. The proposed control strategy regulates simultaneously both PA and PW (i.e., PA/PW modulation). A HOSM controller is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…where λ c was defined in (14). Following the procedure described in [20] allows the solution of (21) to be determined as…”
Section: B Closed-loop Error Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…where λ c was defined in (14). Following the procedure described in [20] allows the solution of (21) to be determined as…”
Section: B Closed-loop Error Systemmentioning
confidence: 99%
“…Past FES-cycling control methods have utilized linear controllers [9]- [11], fuzzy logic and sliding mode controllers [12]- [14], or controllers based on experimental data or numerical optimizations [15]- [18]. All of these previous studies lack detailed stability analyses or require exact model knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Jaime et al proposed a method of generating standing motion using FES by employing proportional-integral-derivative (PID) control [3]. Farhoud et al proposed a pedaling operation based on an FES system composed of a sliding mode controller and a fuzzy mode controller [4]. Bouton et al reported a method of generating desired actions read from electroencephalogram (EEG) by using FES [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Hammerstein model [20], and a few subsequent improvement have been reported [21] [22]. For control using FES, a method using voltage control [6] [8] [18] and a method using current control [4] [15] [16] have been mixed, but it was not reported as to which value determines the exerted force.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches have been taken in attempt to improve the efficiency and power output of FEScycling, including optimization of the cycling mechanism [5], [6], alteration of the stimulation pattern [7]- [11], and variation of the stimulation strategy [12]- [15]. Studies have explored the use of feedback control methods to automatically determine the appropriate stimulation parameters, but most use either linear approximations of the nonlinear cycle-rider system [16] or nonlinear methods lacking detailed stability analyses [17]- [19]. Previous approaches (cf.…”
Section: Introductionmentioning
confidence: 99%